2016
DOI: 10.1126/scisignal.aad5578
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Reelin protects against atherosclerosis by reducing leukocyte–endothelial cell adhesion and lesion macrophage accumulation

Abstract: The multimodular glycoprotein Reelin controls neuronal migration and synaptic transmission by binding to Apolipoprotein E receptor-2 (Apoer2) and very low-density lipoprotein receptor (Vldlr) on neurons. In the periphery, Reelin is produced by the liver, circulates in blood and promotes thrombosis and hemostasis. To investigate if Reelin influences atherogenesis we studied atherosclerosis-prone low-density lipoprotein receptor-deficient (Ldlr−/−) mice in which we inducibly deleted Reelin either ubiquitously or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 60 publications
(90 reference statements)
1
46
0
Order By: Relevance
“…The transcription factor NF‐kB is associated with activation of inflammatory pathways and the onset of atherosclerosis . In fact, the expression of VCAM‐1 and ICAM‐1 in atherosclerotic lesions is principally controlled by NF‐kB . Our results showed that the NF‐kB pathway participates in cholesterol‐induced VSMC damage.…”
Section: Discussionmentioning
confidence: 57%
“…The transcription factor NF‐kB is associated with activation of inflammatory pathways and the onset of atherosclerosis . In fact, the expression of VCAM‐1 and ICAM‐1 in atherosclerotic lesions is principally controlled by NF‐kB . Our results showed that the NF‐kB pathway participates in cholesterol‐induced VSMC damage.…”
Section: Discussionmentioning
confidence: 57%
“…Of note, many neuropsychiatric diseases have been associated with dysregulated Reelin expression, including schizophrenia, depression, autism, temporal lobe epilepsy, and neurodegenerative disease (Impagnatiello et al, 1998 ; Guidotti et al, 2000 ; Fatemi, 2001 ; Persico et al, 2001 ; Haas et al, 2002 ; Sáez-Valero et al, 2003 ; Botella-López et al, 2006 ; Knuesel, 2010 ; Folsom and Fatemi, 2013 ). Reelin-responsive cells outside the central nervous system remain mostly elusive, although significant amounts of Reelin are detected in plasma and various non-neuronal tissues (Ikeda and Terashima, 1997 ; Smalheiser et al, 2000 ; Kobold et al, 2002 ; Lugli et al, 2003 ; Botella-Lopez et al, 2008 ), and functional effects of Reelin on blood cells such as platelets (Tseng et al, 2014 ), endothelial cells (Ding et al, 2016 ), or pancreatic cancer cell lines (Sato et al, 2006 ) have been described.…”
Section: Physiological Roles Of Reelinmentioning
confidence: 99%
“…Many of the non-canonical Reelin-receptor interactions are possibly related to the expression of Reelin outside the brain, which has first been acknowledged shortly after the Reelin gene was discovered (Ikeda and Terashima, 1997 ). Various tissues and organs contain Reelin at relatively high concentrations, including plasma, blood cells, liver and intestine (Smalheiser et al, 2000 ; Lugli et al, 2003 ; Underhill et al, 2003 ; García-Miranda et al, 2010 ; Böttner et al, 2014 ; Ding et al, 2016 ), and altered expression, glycosylation and processing of peripheral Reelin under pathophysiological conditions has been described (Botella-Lopez et al, 2008 ). Moreover, an association of (mostly reduced) Reelin expression and malignancy of various tumors has been reported, even in tissues that normally do not express Reelin, which suggests a possible role in the control of tumorigenesis and/or metastasis via unknown mechanisms (Wang et al, 2002 ; Sato et al, 2006 ; Perrone et al, 2007 ; Dohi et al, 2010 ; Stein et al, 2010 ; Okamura et al, 2011 ; Castellano et al, 2016 ; Lin et al, 2016 ).…”
Section: Summary and Perspectivementioning
confidence: 99%
“…29,32 Recent work from our group showed that apoER2 mediates Reelin signaling in endothelial cells and macrophages to promote vascular inflammation and atherosclerosis. 42 The receptor in the endothelium also binds to apolipoprotein E (apoE). We have shown that, upon binding of apoE3, a common apoE allele associated with cardioprotective phenotype in human, apoER2 stimulates eNOS and cell migration.…”
Section: Apoer2 In the Pathogenesis Of The Antiphospholipid Syndromementioning
confidence: 99%